2016
DOI: 10.1128/jb.00849-15
|View full text |Cite
|
Sign up to set email alerts
|

Permuting the PGF Signature Motif Blocks both Archaeosortase-Dependent C-Terminal Cleavage and Prenyl Lipid Attachment for the Haloferax volcanii S-Layer Glycoprotein

Abstract: For years, the S-layer glycoprotein (SLG), the sole component of many archaeal cell walls, was thought to be anchored to the cell surface by a C-terminal transmembrane segment. Recently, however, we demonstrated that the Haloferax volcanii SLG C terminus is removed by an archaeosortase (ArtA), a novel peptidase. SLG, which was previously shown to be lipid modified, contains a C-terminal tripartite structure, including a highly conserved proline-glycine-phenylalanine (PGF) motif. Here, we demonstrate that ArtA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…In previous work, we demonstrated that the H. volcanii ArtA is required for the processing and lipidation of substrates that contain a conserved PGF C‐term tripartite structure (Abdul Halim et al ., ). While conserved amino acids that may be critical for ArtA catalytic activity had been predicted in silico (Haft et al ., ), the catalytic site remained uncharacterized in vivo .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In previous work, we demonstrated that the H. volcanii ArtA is required for the processing and lipidation of substrates that contain a conserved PGF C‐term tripartite structure (Abdul Halim et al ., ). While conserved amino acids that may be critical for ArtA catalytic activity had been predicted in silico (Haft et al ., ), the catalytic site remained uncharacterized in vivo .…”
Section: Resultsmentioning
confidence: 97%
“…Recently, a novel surface protein anchoring mechanism in prokaryotes was identified, in which substrates containing a C‐terminal tripartite structure, reminiscent of the sortase substrate tripartite structure, are C‐terminally processed, but unlike sortase A substrates, are then anchored to the cytoplasmic membrane (Abdul Halim et al ., ). The enzymes involved in this process, archaeal archaeosortases and bacterial exosortases, were identified using in silico phylogenetic profiling analysis of genomes that also encode proteins having a C‐terminal tripartite architecture with variations on the LPXTG motif (Navarre and Schneewind, ; Haft et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In archaea, S-layer proteins are most often attached to the cell membrane. S-layer proteins can be anchored to the membrane via a C-terminal transmembrane helix domain (3, 9) or covalently attached to cell membrane lipid via an archaeosortase, as shown in Haloferax volcanii (10,11). In most microorganisms, the S-layer is composed entirely of one or two proteins (SLPs), which self-assemble.…”
mentioning
confidence: 99%